Alley cropping with Leucaena leucocephala (Lam) de Wit and Acioa barteri (Hook F.) Engl. - Siaw, D.E.K.A.; Kang, B.T.; Okali, D.U.U. (1991)
The effect of alley cropping with seven combinations of Acioa and Leucaena hedgerows and a control (no hedgerow) treatment on sequentially cropped maize and cowpea was studied in 1985 and 1986. The trial was carried out on an Alfisol in the humid zone of southwestern Nigeria. Hedgerows were established in 1983, using 4 m interhedgerow spacing and pruned to 25 cm height during cropping. Highest dry matter, wood, and nutrient yields of prunings of Acioa and Leucaena hedgerows were obtained with sole cropping. Growing Leucaena and Acioa in the same hedgerow suppressed dry matter production and nutrient yield of Acioa more than of Leucaena owing to the latter's faster growth. Total pruning dry matter yield was reduced as the proportion of Acioa increased in the combination. Leucaena prunings had higher nutrient yield than Acioa. Under 22-month old uncut hedgerows, weed biomass declined in the presence of Leucaena, either alone or in combination with Acioa. Weed weight under sole Leucaena hedgerows was about a third of that in the control plot. There was no significant effect of alley cropping on weed biomass, although alley cropping with Acioa and Leucaena hedgerows resulted in the dominance of broad leaf weeds while the control had a mixture of broadleaves and grasses. Alley cropping with various combinations of Acioa and Leucaena hedgerows increased maize and cowpea yields compared to control. Nitrogen application in both years increased maize grain yield. Mean yield increase due to N application in both years was highest in the control (47.2%) followed by the sole Acioa hedgerow (25.2%) and less in hedgerows with Leucaena. The results of observations over two years do not show any advantage for the tested Leucaena and Acioa combinations on maize and cowpea crops as compared to the sale hedgerows.